. The Diagnostic Value plasma procalcitonin (PCT) and serum amyloid A protein (SAA) in Children with Mycoplasma Pneumonia: Diagnostic Value plasma procalcitonin (PCT) and serum amyloid A protein (SAA) - Zheng, Yao (Journal of Medical Biochemistry, 2025)
Objective: To evaluate the diagnostic value of pulmonary ultrasound combined with plasma procalcitonin (PCT) and serum amyloid A protein (SAA) in children with Mycoplasma pneumoniae pneumonia (MPP). Method: Clinical data of 80 children with community-acquired pneumonia admitted to our hospital from January 2023 to December 2023 who underwent lung ultrasound examination were collected. Children with MPP were divided into MPP group and non MPP group on the ground of whether they were MPP patients. PCT and SAA levels were checked meanwhile, and lung ultrasound and PCT and SAA examination results were collected and compared. The ROC curve was used to evaluate the value difference of the three alone and in combination in the diagnosis of mycoplasma pneumonia. Result: Compared with non MPP, MPP children showed significant differences in multiple aspects of lung ultrasound imaging, PCT, and SAA levels. Logistic regression analysis further indicated that individuals with increased/fused B-lines, elevated PCT, and elevated SAA had a lower risk of MPP, while a small amount of pleural effusion was a risk factor for MPP. The logistic regression model established on the ground of the above four variables had good predictive value for MPP. Conclusion: Abnormal imaging features of lung ultrasound, such as increased/fused B-lines, small amounts of pleural effusion, and PCT and SAA levels, are associated with the occurrence of MPP in children. A small amount of pleural effusion indicates a higher risk of disease as MPP. Detecting PCT, SAA levels, and lung ultrasound can promote the improvement of accuracy in distinguishing early MPP from non MPP.